Zur Berücksichtigung von Scherung und Umschlagwinkel bei der Neigungsmessung mit zweiachsigen Neigungssensoren - Hirt, Christian (Wittwer, 2008)
This paper deals with a new rigorous transformation model for (plumb line referred) tilt measurements using two-axial inclination sensors in two observation directions. The approach accounts for deviations from the perpendicular orientation of the two sensor axes as well as for misalignment between both observation directions. The model requires numerical values both for the shearing between the sensor axes and for the misalignment between both observation directions. Formulae are derived which can be applied for precise tilt measurements performed in two observation directions.